Virtual blood bank - Kit Fai Wong (Elsevier, 2011)
Virtual blood bank is the computer-controlled, electronically linked information management system that allows online ordering and real-time, remote delivery of blood for transfusion. It connects the site of testing to the point of care at a remote site in a real-time fashion with networked computers thus maintaining the integrity of immunohematology test results. It has taken the advantages of information and communication technologies to ensure the accuracy of patient, specimen and blood component identification and to enhance personnel traceability and system security. The built-in logics and process constraints in the design of the virtual blood bank can guide the selection of appropriate blood and minimize transfusion risk. The quality of blood inventory is ascertained and monitored, and an audit trail for critical procedures in the transfusion process is provided by the paperless system. Thus, the virtual blood bank can help ensure that the right patient receives the right amount of the right blood component at the right time.